RANCANG BANGUN WEB SERVICE E-BUDGETING GEREJA TORAJA JEMAAT BINTARO MENGGUNAKAN METODE RESTFUL API BERBASIS WEB DAN ANDROID - Hayati, Putri; Harsanto, Kukuh; Aulawi, Muhammad Iqbal; Wanda, Febri; Subandi, Subandi (Universitas Budi Luhur, 2025)
The church is a place of worship for Christians. In carrying out worship and service activities every week there are a number of cash receipts and cash expenditures. Currently, the Toraja Jemaat Bintaro Church is still recording cash out and in manually. With the creation of web applications that can facilitate the church in recording cash and android applications that provide financial information to the congregation. This web and android application will be created using the RESTful API method with android and web based, the web API will provide the data requested from the web and android applications. This method can also ensure the data provided to the congregation and in accordance with the database in the church. This application uses PHP, HTML, CSS and Dart programming languages. The API and web of this application use the Laravel framework while the android application is made with the flutter framework E-budgeting applications can simplify the process of managing donation, tithe, and budget data at the Toraja Jemaat Bintaro Church because the E-budgeting application makes church data collection processed accurately, efficiently, and saves time. This application can also provide more effective and efficient donation, tithe, and budget information for congregations that can be accessed at any time without the need to wait for the congregational newsletter that will be given every week.